Cyanobacterium Raphidiopsis raciborskii and its toxin in Buon Phong reservoir, Dak Lak province, Vietnam - Ngo Thi Diem, My; Ton That, Phap; Duong Thi, Thuy; Le Thi Phuong, Quynh; Nguyen Thi Thu, Lien (Vietnam Journal of Earth Sciences, 2022)
This study investigated the variation of the cyanobacterium Raphidiopsis raciborskii population under the influence of physicochemical parameters from May 2019 to April 2020 in the Buon Phong reservoir. The correlations between these parameters were explored by using Principal Component Analysis (PCA) and Pearson correlation analysis. The cylindrospermopsin (CYN) toxin in isolated strains from the reservoir was confirmed by using High-performance liquid chromatography (HPLC) analyses. R. raciborskii presented throughout the year in the reservoir with a biovolume from 0.12 to 9.14 mm3 L-1. Four R. raciborskii strains (CBP2, CBP3, CBP4, and CBP5) were successfully isolated and confirmed to produce CYN by the HPLC results. The highest concentration in isolated strains was 0.345 μg g-1 DW in the CBP4 strain. The PCR results of genes responsible for CYN biosynthesis showed that the PCR amplicons of cyrB and CyrC were amplified in two toxic strains (CBP2 and CBP3), while the amplicons of both cyrB and cyrC were not observed in two remaining toxic strains. In addition, such abiotic factors as temperature and nutrients played major roles in the abundance of R. raciborskii. Moreover, the biovolume of R. raciborskii positively correlated with the CYN concentrations in the Buon Phong reservoir.